The concept of human dignity in the case law of the National Supreme Court of Justice (Prudentia Iuris, 2017)
The concept of dignity comprises various meanings. Its legislative adoption started with the birth of the Argentine Nation. There is a case law that shows the vast array of subjects in which the concepts of dignity and human dignity have been applied. Said case law also demonstrates that, within one meaning, various senses of human dignity may have been resorted to. The various senses cannot leave aside the hard core of the concept, linked to human beings under no distinction.
Keywords: Human dignity; Case law; Human beings